1995
DOI: 10.2307/2996452
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Structure and Composition of Southern Appalachian Riparian Forests

Abstract: structure and composition of Southern Appalachian riparian forests. Bull. Torrey Bot. Club 122: 134-144. 1995.-Vegetative characteristics of twelve Southern Appalachian riparian forests were sampled as part of a larger study which examined functional attributes of riparian zones. Riparian forests were representative of the mixed mesophytic forest, eastern hemlock forest, and transitions between these types. Early-and mid-successional stages were generally dominated by an overstory of pioneering shade-intoleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
13
0
5
Order By: Relevance
“…While seedlings are establishing beneath a R. maximum understory, recruitment to the larger sapling classes appears to be limited by the extent of this cover. Other studies conducted in southern Appalachian forests have reported similar findings with reduced tree regeneration or lack of recruitment in understories dominated by R. maximum (Phillips and Murdy 1985;Monk et al 1985;Hedman and Van Lear 1995;Rivers et al 2000;Van Lear et al 2002). Van Lear et al (2002) did report successful T. canadensis seedling establishment in areas of moderately dense R. maximum cover, but even in these locations, regeneration was greatest where R. maximum coverage was lowest.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…While seedlings are establishing beneath a R. maximum understory, recruitment to the larger sapling classes appears to be limited by the extent of this cover. Other studies conducted in southern Appalachian forests have reported similar findings with reduced tree regeneration or lack of recruitment in understories dominated by R. maximum (Phillips and Murdy 1985;Monk et al 1985;Hedman and Van Lear 1995;Rivers et al 2000;Van Lear et al 2002). Van Lear et al (2002) did report successful T. canadensis seedling establishment in areas of moderately dense R. maximum cover, but even in these locations, regeneration was greatest where R. maximum coverage was lowest.…”
Section: Discussionmentioning
confidence: 53%
“…Canopy gap formation also allows for the expansion of R. maximum (Runkle 1982), and this species appears to be increasing in cover in the southern Appalachian Mountains (Dobbs and Parker 2004). While T. canadensis seedlings can establish beneath a R. maximum understory, recruitment to the larger size-classes is limited by the extent of this cover (Monk et al 1985;Hedman and Van Lear 1995;Van Lear et al 2002). Therefore, future forest composition may be significantly less diverse without prescriptive management of R. maximum densities.…”
Section: Management Considerationsmentioning
confidence: 95%
“…The large proportion of stems in smaller GLD classes might be taken as evidence that rhododendron probably will continue to dominate both the Yayla and Devrek sites in the future. Rhododendron proliferates vigorously (Cross, 1981;Shaw, 1984;Eyuboglu and Karadeniz, 1987;Esen and Zedaker, 2004) and exponentially in population size after disturbances (Monk et al, 1985;Baker, 1994;Dobbs, 1995;Hedman and Van Lear, 1995). Lesser recruitment was indicated by both GLD and age-class distributions of the rhododendron population at…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, the results of this research in conjunction with others (Rooney et al 2000;Kincaid 2008, submitted) have elucidated a link between canopy openness or disturbance and Tsuga canadensis regeneration. Because Rhododendron maximum has been shown to invade canopy gaps easily (Ploucher and Carvell 1987;Dobbs and Parker 2004), and it is well known that this species often precludes the regeneration of Tsuga canadensis, as well as other tree species (Monk et al 1985;Hedman and Van Lear 1995;Van Lear et al 2002), any silvicultural treatment resulting in canopy gap creation may also have to include Rhododendron maximum removal to further promote tree regeneration. The baseline information provided by this research and future studies can aid land managers in the promotion of Tsuga canadensis regeneration in areas where treatment against hemlock woolly adelgid infestation is successful.…”
Section: Disturbance Regimesmentioning
confidence: 98%